Qualitative Descriptive Research Investigating Burn Survivors’ Perspectives on Quality of Care Aspects - Raaba S. M. Thambithurai; Lotte van Dammen; Margriet E. van Baar; Hendriët Wanders; Angelique E. A. M. Weel-Koenders; Tsjitske M. Haanstra; Carine M. H. van Schie; Paul P. M. van Zuijlen; Cornelis H. van der Vlies; Eelke Bosma; Corine A. Lansdorp; Inge Spronk; et al. (European Burn Journal, 2024)
Burn care quality indicators are used to monitor and improve quality of care and for benchmark purposes. The perspectives of burn survivors, however, are not included in current sets of quality indicators while patient-centred care gains importance. The aim of this study was to explore burn survivors’ perspectives on quality aspects of burn care, which was used to translate their perspectives into patient-centred quality of care indicators. Qualitative descriptive research was conducted in a patient panel group. First, thematic analysis was applied to the focus groups to identify overarching themes. Second, patient-centred quality indicators, informed by burn survivors’ valued aspects of care, were defined. Ten burn survivors with an average age of 54 years (SD = 11; range 38–72 years) and mean TBSA burned of 14% (SD = 11%; range 5–35%) participated in two focus groups. Four overarching themes were identified, pointing to the importance of (1) information tailored to the different phases of recovery, (2) significant others’ wellbeing and involvement, (3) a therapeutic relationship and low-threshold access to healthcare professionals and (4) to participate in decision-making. Eighteen patient-centred process quality of care indicators within nine aspects of care were formulated. The overarching themes are reflected in patient-centred quality indicators, which present a broadened and complementary view of existing clinical quality indicators for burn care. Evaluating these patient-centred quality indicators may increase quality of care and refine patient-centred care.